An intentional approach to risk management processes and methods and the impact of the recent financial crisis. - Protopapas, Nikolas (2008)
Purpose In a first stage this research attempt to explored the phenomenon of financial crisis and the risk management procedures and methods of the banking industry. Secondly the author attempts to examine the risk management differences and similarities, in four different countries. . Design/methodology/approach The conducted research comprises, four (4) case studies, interviews and the creation of descriptive statistics as a complementary element for a more comprehensive understanding